Animation, Simulation and Internet Based Measurement of a DC Servo System in Distant Learning - Széll, Károly; Sziebig, Gábor (Acta Agraria Kaposváriensis, 2007)
The paper presents a complete (animation, simulation and internet based measurement) multimedia educational program of DC servo system for distant learning. The animation program describes the basic operation of a DC motor, derives the torquespeed characteristics and explains the basic steps of control design. The animation program includes screens for teaching in class and for individual study as well. With the guidance of this animation program the students can simulate the control of a given servo system. The final and most important step in any kind of education in the field engineering is the measurement. This is the most challenging step in distant learning. The students should enter to a web page to access the experimental set up. The administration, queuing arranged by a C# based program. The experimental set up includes a DC servo motor with 4 quadrant drive. The drive can be switch on and off via internet. The students can write a simple PI or sliding mode controller program which is inserted into the communication frame program to operate the servo motor. The measurement result is generated in such form which is compatible to the simulation results the students can compare their simulation and measurement results.